Relationship between oral microbiota, oral hygiene and dental caries in children with diabetes mellitus - Flores Quiroz , Gabriel (2025)
Diabetes mellitus (DM) is a growing health problem, with a total of 463 million people worldwide suffering from it. This figure is expected to reach 578 million by 2030. The objective is to conduct a narrative review and determine the relationship between oral microbiota, oral hygiene and dental caries in children with diabetes mellitus. For the narrative review, a bibliographic search was carried out to select academically certified information from articles extracted from the Scopus database, with a sample of 50 articles organized in the atlas.ti program. Children with DM are more likely to suffer from dental problems such as tooth decay, this may be influenced by a high prevalence of bacteria and poor oral hygiene habits.